Fabrication and characterization of kesterite Cu2ZnSnS4 thin films deposited by electrostatic spray assisted vapour deposition method. Issue 1 (21st August 2014) - Liu, J. P.; Choy, K. L.; Placidi, M.; López‐García, J.; Saucedo, E.; Colombara, D.; Robert, E.
<x xml:space="preserve">Abstract</x> Most of the high efficiency kesterite solar cells are fabricated by vacuum or hydrazine‐based solution methods which have drawbacks, such as high cost, high toxicity or explosivity. In our contribution, an alternative non‐vacuum and environmental friendly deposition technology called electrostatic spray assisted vapour deposition (ESAVD) has been used for the cost‐effective growth of Cu2ZnSnS4 (CZTS) thin films with well controlled structure and composition. CZTS films have been characterized using a combination of XRD, XPS, SEM‐EDX, AFM, and Raman spectroscopy. The results demonstrated that adherent, uniform and homogeneous CZTS films without apparent secondary phases have been produced by ESAVD. The atomic ratios measured by EDX are Cu/(Zn + Sn) = 0.88 and Zn/Sn = 1.17, which are very close with the reported high efficiency solar cells and can be finely tuned by formulating the precursor.CZTS films exhibited a typical optical band gap of 1.53 eV from UV–Vis analysis. Cu2ZnSnS4 produced by the ESAVD are being optimized towards the fabrication of high efficiency photovoltaic devices.